The Diaries of John Gregory Bourke Vol 4 : July 3, 1880--May 22, 1881. - Bourke, John Gregory (University of North Texas Press, 2009)
John Gregory Bourke kept a set of diaries as aide-de-camp to Brigadier General George Crook. This fourth volume chronicles the political and managerial affairs in Crook's Department of the Platte. It focuses on the controversy concerning the forced relocation of the Ponca Indians from their ancient homeland along the Dakota-Nebraska line.